Optimization of Clean Water Supply through Community Assistance in Preparing the Budget Plan for Domestic Water Channel Rehabilitation in Kelindang Atas Village - Claudia, Rany; Apriansyah, Yudi; Herawati, Afriyastuti; Arfan, Muhammad; Habibullah, Natsir (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2025)
The provision of adequate clean water is a form of fulfilling the basic needs of the community, which is very important for supporting good health and quality of life. Kelindang Atas Village still has problems in the management and rehabilitation of domestic water channels. This community service initiative aims to optimize clean water supply by assisting the community in developing a Cost Estimate Plan (CEP) for the rehabilitation of domestic water supply systems. The methods used include observing the condition of water supply systems, conducting outreach on CEP development, and facilitating group discussions with village residents as partners. The results of the community service initiative demonstrate an increase in community understanding of the planning and budgeting processes for rehabilitation, as well as the development of a realistic and field-appropriate RAB. Resulted in a 60% increase in budgeting accuracy as measured by alignment with field conditions. Active community involvement in the RAB development process through guidance is the key to the success of optimizing clean water supply in Kelindang Atas Village.